Analysis of the Impact of Entrepreneurship Education and Curriculum Innovation on Entrepreneurial Motivation and Student Performance in Private Universities in East Java - Chairunnisa Chairunnisa; Yenik Pujowati; Tera Lesmana (Westscience Press, 2025)
This study examines the impact of Entrepreneurship Education and Curriculum Innovation on Entrepreneurial Motivation and Student Performance in private universities in East Java. Using a quantitative research design with a sample of 180 students, data were collected using a Likert scale (1-5) and analyzed with Structural Equation Modeling (SEM-PLS 3). The results indicate that Curriculum Innovation significantly affects Entrepreneurial Motivation and Student Performance, with Entrepreneurship Education also positively influencing both Entrepreneurial Motivation and Student Performance. These findings highlight the importance of innovative curricula and entrepreneurial-focused education in fostering entrepreneurial attitudes and enhancing academic performance among students. The study provides practical implications for educational institutions, suggesting that continuous curriculum innovation and entrepreneurship education are critical to preparing students for entrepreneurial ventures and improving their overall academic success.